Charge and spin correlations in the monopole liquid - Slobinsky, Demian Gustavo (2018)
A monopole liquid is a spin system with a high density of magnetic charges but no magnetic-charge order. We study such a liquid over an Ising pyrochlore lattice, where a single topological charge or monopole sits in each tetrahedron. Restricting the study to the case with no magnetic field applied we show that, in spite of the liquidlike correlations between charges imposed by construction constraints, the spins are uncorrelated like in a perfect paramagnet. We calculate a massive residual entropy for this phase (ln(2)/2, a result which is exact in the thermodynamic limit), implying a free Ising-like variable per tetrahedron. After defining a simple model Hamiltonian for this system (the balanced monopole liquid) we study its thermodynamics. Surprisingly, this monopole liquid remains a perfect paramagnet at all temperatures. Thermal disorder can then be simply and quantitatively interpreted as single charge dilution, by the excitation of neutral sites and double monopoles. The addition of the usual nearest neighbors interactions favoring neutral ´2in-2out´ excitations as a perturbation maintains the same ground state but induces short-range (topological) order by thermal disorder. While it decreases charge-charge correlations, pair spin correlations - resembling those in spin ice - appear on increasing temperature. This helps us to see in another light the dipolarlike correlations present in spin ices at unexpectedly high temperatures. On the other side, favoring double excitations strengthens the charges short range order and its associated spin correlations. Finally, we discuss how the monopole liquid can be related to other systems and materials where different phases of monopole matter have been observed.